2020
DOI: 10.1186/s40560-020-00446-3
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte distribution width enhances early sepsis detection in the emergency department beyond SIRS and qSOFA

Abstract: Background: The initial presentation of sepsis in the emergency department (ED) is difficult to distinguish from other acute illnesses based upon similar clinical presentations. A new blood parameter, a measurement of increased monocyte volume distribution width (MDW), may be used in combination with other clinical parameters to improve early sepsis detection. We sought to determine if MDW, when combined with other available clinical parameters at the time of ED presentation, improves the early detection of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 36 publications
6
49
1
1
Order By: Relevance
“…A recent study has shown the usefulness of MDW plus clinical scores [ 30 ]. Crouser et al [ 30 ] have shown that normal MDW combined with SIRS or qSOFA reduced the probability of sepsis and suggested MDW as complimentary marker to clinical scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown the usefulness of MDW plus clinical scores [ 30 ]. Crouser et al [ 30 ] have shown that normal MDW combined with SIRS or qSOFA reduced the probability of sepsis and suggested MDW as complimentary marker to clinical scores.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown the usefulness of MDW plus clinical scores [ 30 ]. Crouser et al [ 30 ] have shown that normal MDW combined with SIRS or qSOFA reduced the probability of sepsis and suggested MDW as complimentary marker to clinical scores. In this analysis, when combined with a clinical score (qSOFA), MDW showed a significantly improved diagnostic accuracy in terms of AUC in the overall population ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that changes in volume of monocytes are a well-documented consequence of monocyte activation upon bloodstream infections as part of innate immunity response [25,26]. To date, four large clinical studies investigated the ability of MDW to predict sepsis, but they enrolled only patients in Emergency Departments [15,22,28,29]. Crouser et al demonstrated that MDW was able to discriminate sepsis from SIRS and that the magnitude of MDW elevations correlated with infection severity and organ dysfunction, with MDW values rising in parallel with the severity of ensuing sepsis [15].…”
Section: Discussionmentioning
confidence: 99%
“…Crouser et al demonstrated that MDW was able to discriminate sepsis from SIRS and that the magnitude of MDW elevations correlated with infection severity and organ dysfunction, with MDW values rising in parallel with the severity of ensuing sepsis [15]. Recently, Crouser et al (2020) demonstrated that inclusion of MDW during the initial evaluation of ED patients may enhance the odds of early sepsis detection by 6-fold for Sepsis-2 and 4-fold for Sepsis-3 assessments [28]. An additional prospective study described, for the rst time, the ability of MDW to predict sepsis in a cohort of 260 consecutive patients hospitalized in an Infectious Diseases ward.…”
Section: Discussionmentioning
confidence: 99%
“…Large administrative data analyzed by the SEPSIS-3 authors suggested that a qSOFA score of ≥ 2 would rapidly identify non-ICU patients “more likely to have poor outcomes typical of sepsis,” defined as in-hospital mortality > 10%, with an area under the receiver operating characteristic (AUROC) curve of 0.81 (compared to 0.76 for the SIRS criteria; p = 0.01) 1 , 15 . The authors concluded that the new definitions should “facilitate earlier recognition and more timely management of patients with sepsis or at risk of developing sepsis 1 .” Since this assertion in 2016, numerous authors have analyzed the usefulness of qSOFA in retrospective and prospective cohorts at different points in the care continuum from pre-hospital 16 , 17 to initial triage 18 20 to the period of ED management 20 , 21 to in-patient wards and the ICU 15 ; have looked at it as a screening tool for all patients presenting to the ED 22 or for those with suspected infection 23 , 24 ; have investigated dynamic changes in qSOFA during ED stay 20 , 25 ; have analyzed its accuracy as a predictor of ICU admission, length of stay, and in-hospital mortality 26 ; have tried to improve the performance of qSOFA by add various biomarkers including lactate 27 , 28 , procalcitonin 29 , monocyte distribution width 30 , and CRP combined with mid-regional proadrenomedullin 31 or vital sign measures including heart rate variability 32 , EtCO 2 33 , and shock index 19 ; have examined its utility in high and low resource settings 27 , 29 , 34 ; and have compared it to other scoring systems including SIRS, MEWS, NEWS, and conventional SOFA 35 , 36 . All of these studies provide important clinical information and have various limitations mainly related to the data sets used, the presence or absence of serial qSOFA values, the clinical setting where the studies were performed, and the overall mortality of the cohorts.…”
Section: Introductionmentioning
confidence: 99%